Analysis of Student Activity and Learning Outcomes in 21st-Century Innovative Learning with the PjBL Learning Model in 5th Grade of Elementary School - Istikomah Istikomah; Ana Andriani (Proceedings Series on Social Sciences & Humanities, 2025)
This study began with observations at SDN Cinangsi 03, which revealed low student engagement in learning due to the limited application of 21st-century innovative approaches. The aim of this research, conducted in a 5th-grade elementary school, is to analyze the impact of project-based learning on student activity and learning outcomes on the topic "Magnet, Electricity, and Technology for Life." The study employs a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The results show that the implementation of project-based learning significantly enhances student engagement and fosters 21st-century skills, such as creativity, collaboration, and communication. Additionally, most students exhibited an improvement in positive attitudes during the learning process, including responsibility, teamwork, and active participation. These findings suggest that the PjBL model is recommended as an effective teaching approach for creating interactive, enjoyable, and meaningful learning experiences in elementary education.